Schizophrenia in males of cognitive performance: discriminative and diagnostic values Esquizofrenia em homens pelo desempenho cognitivo: valor discriminativo e diagnóstico - Analuiza Camozzato; Márcia L F Chaves (Universidade de São Paulo, 2002)
OBJECTIVE: To evaluate the discriminative and diagnostic values of neuropsychological tests for identifying schizophrenia patients. METHODS: A cross-sectional study with 36 male schizophrenia outpatients and 72 healthy matched volunteers was carried out. Participants underwent the following neuropsychological tests: Wisconsin Card Sorting test, Verbal Fluency, Stroop test, Mini Mental State Examination, and Spatial Recognition Span. Sensitivity and specificity estimated the diagnostic value of tests with cutoffs obtained using Receiver Operating Characteristic curves. The latent class model (diagnosis of schizophrenia) was used as gold standard. RESULTS: Although patients presented lower scores in most tests, the highest canonical function for the discriminant analysis was 0.57 (Verbal Fluency M). The best sensitivity and specificity were obtained in the Verbal Fluency M test (75 and 65, respectively). CONCLUSIONS: The neuropsychological tests showed moderate diagnostic value for the identification of schizophrenia patients. These findings suggested that the cognitive impairment measured by these tests might not be homogeneous among schizophrenia patients. OBJETIVO: Avaliar os valores discriminativos e diagnósticos de testes neuropsicológicos na identificação de pacientes com esquizofrenia. MÉTODOS: Estudo transversal com 36 pacientes ambulatoriais esquizofrênicos masculinos e 72 voluntários saudáveis pareados. Os testes neuropsicológicos usados foram o Wisconsin Card Sorting Test, Fluência Verbal, teste de Stroop, Mini Exame do Estado Mental e Span de reconhecimento espacial. Valores diagnósticos dos testes foram estimados por sensibilidade e especificidade, com os pontos de corte obtidos através da curva ROC (Receiver Operating Characteristic). O modelo de classe latente (diagnóstico de esquizofrenia) foi aplicado como padrão ouro. RESULTADOS: Embora os pacientes tenham apresentado escores inferiores na maioria dos testes, a função canônica mais alta pela análise discriminante foi 0,57 (na fluência verbal com a letra M). Os melhores valores de sensibilidade e especificidade foram obtidos pelo teste de fluência verbal com a letra M (75 e 65, respectivamente). CONCLUSÕES: Os testes neuropsicológicos demonstraram valores diagnósticos moderados na identificação de pacientes com esquizofrenia. Os achados sugerem que o prejuízo cognitivo, medido por esses testes, pode não ser homogêneo entre os pacientes esquizofrênicos.